2009
DOI: 10.2209/tdcpublication.50.31
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Orthokeratinized Odontogenic Cyst Suspected to be a Radicular Cyst

Abstract: This report describes a case of orthokeratinized odontogenic cyst arising in the mandibular molar region of a 39-year-old man. Under the initial clinical diagnosis of radicular cyst, root canal treatment was performed on the mandibular right second molar. The treatment that continued for six months did not achieve healing. Subsequently surgical intervention was selected since the tooth fracture was found, and the prognosis was judged to be poor. After atraumatic tooth extraction, the apical cystic lesion was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
10
0
6
Order By: Relevance
“…Wright and Wysocki18 emphasised that OKC should also be included in the differential diagnosis of radiolucencies occurring in the periapical region of non-vital tooth. Onuki et al 19 reported a case of OOC which was suspected to be a radicular cyst. Cyntia et al 20 highlighted the importance of including OOC in the differential diagnosis of developmental odontogenic cysts with secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…Wright and Wysocki18 emphasised that OKC should also be included in the differential diagnosis of radiolucencies occurring in the periapical region of non-vital tooth. Onuki et al 19 reported a case of OOC which was suspected to be a radicular cyst. Cyntia et al 20 highlighted the importance of including OOC in the differential diagnosis of developmental odontogenic cysts with secondary infection.…”
Section: Discussionmentioning
confidence: 99%
“…OOCs are difficult to diagnose due to lack of specific clinical and radiographic characters. [2] A total of 48% of OOCs were discovered as incidental findings, 41% first presented with swellings and 24% first presented with pain. [1] A predilection for the mandible, particularly the posterior sextants (68%) has been reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It appears to represent an uncommon but consistent group of odontogenic developmental cysts that cannot be classified as other established cyst types and should therefore constitute a separate clinical entity. [2]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. 38 casos -Somente aumento de volume 17,20,21,[23][24][25][26][28][29][30]35,[39][40][41][46][47][48]52,53,56,59,63,64,67,[70][71][72]75,81,89,92 ; 2. Aumento de volume associado a:…”
Section: Aspectos Clínicos Iniciaisunclassified